Interdisciplinary Treatment Approach of Skeletal Class III Malocclusion Patient with Multiple Missing Teeth: A Case Report - Halim, Himawan; Halim, Ivan Anthony (Indonesian Journal of Prosthodontic, 2021)
A 30 years old female patient with Class III malocclusion and several missing maxillary anterior and posterior teeth and also mandibular posterior teeth came to the clinic to improve both her esthetic and function. Patient had a unilateral cleft lip and palate. History of combination between poor dental hygiene and dentistry was the cause of the multiple missing teeth. Periodontic, orthodontic, oral maxillofacial surgery and prosthodontics treatments were undertaken in the proper timing and sequence with an interdisciplinary approach. Proper diagnosis and treatment planning were crucial to solve this case. After initial periodontal care was completed, orthodontic treatment was completed to prepare her orthognathic surgery. Space consolidation and occlusion correction were also completed to prepare her for final prosthesis post-surgery. Partial denture were delivered by the prosthodontists. As a result, a stable Class I occlusion with good esthetic and function treatment results were achieved. The case showed that proper diagnosis and treatment planning is very important especially in an interdisciplinary treatment of Class III malocclusion.